I Might Stay to Myself: Activation and Avoidance of Assistance from Kin. Issue 5 (8th April 2020) - Mazelis, Joan Maya; Mykyta, Laryssa
Abstract: Objective: This study explores how low‐income mothers and fathers who recently have had a child avoid and access financial and other instrumental support from kin, and the statements they make about kin support. Background: New parents without significant financial capital have a strong need for social support from family members. Yet some with access to assistance from family do not activate it, and avoiding support can leave them facing dire circumstances alone. Method: This article uses data from all four waves of the Time, Love, and Cash among Couples with Children study (TLC3), a qualitative study embedded in the Fragile Families and Child Wellbeing Study. Researchers used a stratified random sampling scheme to select 25 couples from each of three cities. Analysis used open and axial coding techniques on interview transcript data. Results: Reports of kin support are widespread, but help is not universally activated. Parents often talk in contradictory ways about activating and avoiding support. Those who access help from family often employ the language of avoidance, particularly when it comes to asking for help. Those who avoid it or claim to avoid it say they do so because of individualistic pride, the pressure of reciprocity, and understandings of what it means to be an independent adult. Conclusion: This study illustrates the complexity and contradictions in how participants think and talk about kin support, and demonstrates that having to ask for help presents a key barrier to support.